2020
DOI: 10.3390/nu12041086
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Dietary Glutamine Supplementation Benefits Modulation of Liver Pyroptosis in Mice with Polymicrobial Sepsis

Abstract: The liver is the main organ responsible for bacterial and endotoxin clearance. Pyroptosis is a form of proinflammatory programmed cell death activated by caspase-1/11 and gasdermin D (GadD). Pyroptosis protects the host against bacterial infection; however, overactive pyroptosis can lead to organ injury. Glutamine (GLN) is a specific amino acid with anti-inflammatory and immunomodulatory properties. This study investigated the effects of GLN pretreatment on liver pyroptosis in a mouse model of polymicrobial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Our study revealed for the first time that macrophage Glul has an important protective effect on sepsis that can induce systemic organ failure. Studies have reported that glutamine can relieve different organs of sepsis, such as the intestine, kidney, lung, and liver 29–32 . Therefore, the high fatality rate of sepsis may be due to the different degrees of failure of various organs in the body, and whether Glul, the key enzyme for the synthesis of glutamine, has different alleviating effects on the pathological changes in different organs remains to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed for the first time that macrophage Glul has an important protective effect on sepsis that can induce systemic organ failure. Studies have reported that glutamine can relieve different organs of sepsis, such as the intestine, kidney, lung, and liver 29–32 . Therefore, the high fatality rate of sepsis may be due to the different degrees of failure of various organs in the body, and whether Glul, the key enzyme for the synthesis of glutamine, has different alleviating effects on the pathological changes in different organs remains to be studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Using 18-gauge needle, the exposed cecum was punctured at 2 places. Feces were gently extruded, and cecum was placed back in its anatomical position [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Although a multicenter clinical study revealed that GLN administration was associated with an increased mortality among critical patients with multiorgan failure [ 12 ], subsequent clinical trials found that parenteral GLN supplementation is safe in surgical intensive care unit (ICU) patients and improved outcomes in stabilized patients with organ function [ 13 , 14 ]. Previous studies performed by our laboratory revealed that GLN administration attenuates inflammatory reaction and remote organ injury in sepsis [ 15 17 ]. GLN was found to elicit a more-balanced T helper cell polarization [ 16 ], decreased programmed cell death 1 expression on immune cells [ 18 ], and downregulated high-mobility group box protein-1- (HMGB-1-) mediated pathway [ 19 ], thus alleviating kidney injury in sepsis.…”
Section: Introductionmentioning
confidence: 99%